Sons of Perdition - Measom, Tyler; Merten, Jennilyn (Left Turn Films, 2010)
Verizo FF How many mothers do you have? How many wives would you dream of? A behind-the-scenes look into Warren Jeffs’ polygamous community and the lives of those who decided to escape from it. Remote Colorado City on the Utah-Arizona border is home to the "Crick," a Fundamentalist Latter-Day Saints (FLDS) community. This is the oldest polygamist compound in the United States; here men have several wives and raise their children by the strict code imposed and guarded by the FLDS’ prophet Warren Jeffs. In 2003, Jeffs began a systematic effort to cleanse his flock in preparation for the end of the world. He banned public schooling, gentile books, recreations, and excommunicated all his rivals and critics, marrying their women and children to other men. Hundreds of teenage boys escaped the community, giving up their families and salvation in the hope of an independent life. Sons of Perdition follows three boys after they leave the isolation of Colorado. With limited educations and rarely a stable address, they face enormous obstacles. All the boys have big dreams – starting with the hope of attending high school – yet they long desperately for contact with their families. With unprecedented access, directors Tyler Measom and Jennilyn Merten follow the teenagers for three years after their departure, creating powerful portraits of individualities struggling to be born despite the challenging traumas of the past. A timely, critical look at faith, family and religious exile in mainstream America.